ENERGY CONSUMPTION AND PAYBACK PERIOD ANALYSIS FOR ENERGY-EFFICIENT STRATEGIES IN GLASS TYPE OPTIONS - Aisyah Zakiah (International Journal on Livable Space, 2020)
Cities are facing a challenge with the steady increase in energy consumption for buildings. This study aims to analyse the energy consumption and payback period of energy-efficient strategy implementation in glass type options. The energy-efficient strategy in the glass options is chosen since it affects the energy consumption the most. A study on the payback period needs to be conducted since purchasing high-performance glass materials increase the building capital cost and become a consideration for decision-maker. This study tested 5 variations, including single and double glass windows and incorporating 5 types of glass materials with various solar transmittance properties. The energy consumption then is calculated using energy simulation software OpenStudio using Jakarta weather data. The payback period is calculated to find out the length of time the energy cost saving can recoup the additional capital cost needs to purchase better thermal performance glass. The result shows that the double glass windows with low solar transmittance value reduce the energy consumption for cooling the most. Thus, cheaper glass material with similar solar transmittance value reaches the payback period fastest.